Effects of electromagnetic waves on oocyte maturation and embryonic development in pigs - CHEN, Jia-Si; TSAI, Li-Kuang; YEH, Ting-Yu; LI, Tzai-Shiuan; LI, Cheng-Han; WEI, Zung-Hang; LO, Neng-Wen; JU, Jyh-Cherng (Journal of Reproduction and Development, 2021)
Our living environment has been full of electromagnetic radiation (EMR) due to the prevailing electronic devices and equipment. Intermediate frequency electromagnetic field (IF-EMF) or waves constitute a significant part of EMR; therefore, an increasing number of household electrical appliances have become a source of IF-EMF, and concerns about IF-EMF on health are gaining more attention. However, little information is available about its impact on female reproductive traits, such as germ cell viability and early embryonic development, particularly at the cellular and molecular levels. In this study, we used porcine oocytes as a model system to explore the effect of IF-EMF at various intensities on the in vitro maturation (IVM) of oocytes and their subsequent embryonic development. Our results showed that no difference in oocyte maturation rates was detected among groups, but the cleavage and blastocyst rates of parthenotes derived from EMF-treated oocytes decreased with the weaker IF-EMF intensity (25 and 50 Gauss) groups compared to the control group (P < 0.05). For cytoplasmic maturation, the weaker IF-EMF intensity groups also showed a peripheral pattern of mitochondrial distribution resembling that of immature oocytes and increased autophagy activity. No obvious differences in cytoskeletal distribution and total cell numbers of blastocysts were investigated in the four IF-EMF treatments compared to those in the control group. Although the underlying mechanism associated with EMF effects on oocytes and embryos is still elusive, we have demonstrated that low intensity IF-EMF exerts harmful effects on porcine oocytes during the maturation stage, carrying over such effects to their subsequent embryonic development.